The Use of Virtual Reality to Facilitate Mindfulness Skills Training in Dialectical Behavioral Therapy for Spinal Cord Injury: A Case Study - Flores, Araceli; Linehan, Marsha M.; Todd, S. Rob; Hoffman, Hunter G. (Frontiers in Psychology, 2018)
Abstract. Paralysis from a spinal cord injury (SCI) increases risk of psychological problems including suicide attempts, substance use disorder, negative emotions (e.g., anger), depression, anxiety, ASD/PTSD. Dialectical Behavioral Therapy® (DBT®) has been shown to be effective for treating similar psychological symptoms in non-SCI patient populations. The current study explored for the first time, the feasibility and clinical potential of using Immersive Virtual Reality (VR) enhanced DBT® Mindfulness skills training to help reduce psychological symptoms (negative emotions and anxiety, ASD/PTSD) of two patients with spinal cord injury (SCI). Patient 1 was a 39-year-old male patient suffering multiple spinal cord injuries, resulting in quadriplegia, after falling out of a four story building. Patient 1 had severe depression, and anxiety symptoms. Patient 2, was a 31 year old male with a C7 vertebral body fracture, leading to paresis, after suffering a blunt force trauma injury during an attempted suicide, jumping from a moving vehicle. Patient 2 had mild depression, and anxiety symptoms. Methods: Each patient looked into VR goggles, and had the illusion of slowly “floating down” a river in virtual reality while listening to DBT® Mindfulness Skills training instructions. Each patient filled out brief psychological ratings before and after each VR session, four VR DBT® sessions for patient 1, and two VR DBT® sessions for patient 2. Results: As predicted, patient 1 reported reductions in negative emotions after each VR DBT® Mindfulness session. Patient 2 had mixed results on some of the measures of negative emotions. And both patients reported feeling less depressed, less anxious, and less emotionally upset, after VR DBT® Mindfulness Skills learning. Patient 2 reported large reductions in short term ASD/PTSD symptoms after his first VR DBT® mindfulness skills training session. Conclusion: This study explored the feasibility of using VR DBT® with quadriplegic or paresis SCI patients. Both SCI patients accepted VR, the patients liked using VR, and, with assistance from the therapist, the patients were able to use the VR equipment, despite being paralyzed. Additional research and development will be needed to determine whether VR DBT® Mindfulness Skills training leads to any long term improvements in outcome.